PENYELESAIAN SENGKETA BATAS LAUT ANTARA INDONESIA-MALAYSIA (KASUS PERBUTAN PULAU SIPADAN DAN LIGITAN) - Yohanes Arman; Mathilda Karmenita, Defi Marsela Payung, Arnoldus Bramantio Siwe (INTELIGENSIA MEDIA, 2024)
The dispute between Indonesia and Malaysia relates to the islands of Sipadan and Ligitan, with Malaysia considering the islands of Sipadan and Ligitan to be part of its national territory. Indonesia's position was that it initially wanted to take this matter through the ASEAN High Council, but eventually agreed to resolve this dispute through the International Court of Justice. For this reason, there is a need for a political system that regulates relations between neighboring countries on the surface Earth. This research is normative legal research with a legal case-based approach. By observing various laws related to state territorial boundaries. Regarding the case of Sipadan and Ligitan islands before the International Court of Justice, both parties, both Indonesia and Malaysia, have done persuasive work and convinced the International Court of Justice that they have the right to own the two islands. The ICJ ruled that Malaysia had the right to the islands of Sipadan and Ligitan